Feminisme dalam Novel Sepasang Luka yang Berakhir Duka Karya Ameylia Falensia - Nur Aripa; Sri Rahayu (UIR Press, 2023)
This research focuses on the study of social aspects of feminism which includes the process of socialization, social tasks and social class. This study uses a descriptive qualitative approach and belongs to the type of library research. The data in this study are phrases, clauses, words and paragraphs that contain social aspects of feminism. The results of the data analysis in this study indicate that first in the novel A Pair of Luka that Ends Grief by Ameylia Falensia there is a socialization process that occurs in female characters when interacting with other characters in the novel. The author provides an overview of the socialization process when the female character establishes social relationships with other characters and the impact of the socialization process she goes through on her. The socialization process is found in the Lengkara figure; second, the author describes the social duties of the female character in this novel based on the duties of a woman as a child, wife, mother, housemaid and grandmother. The social task of women is seen from the role of women in their lives. Social tasks are found in the figures of Nina, Afni, Lengkara and Prima; and third, social class is described as a certain position that has a female figure in society. Social class is divided into lower, middle and upper classes. The determination of social class in this novel is divided on the basis of gender, type of work, wealth, level of education and social literature in society. The social class of women in this novel is found in the characters Nilam, Lengkara and Bibi.